Коронатор: [роман] / Симона Вилар - Вилар Симона (Клуб Семейного Досуга, 2012)
Экземпляры: аб. ЦБ (2017.02.05) / Инвентарный номер: 3072 / Цена: / Сис.шифр: 84(4Укр) / Авт.знак: В 44 / ГРНТИ: 17.82.31 / ББК: 84(4Укр)